Influence of polarization angle on LIPSS formation and ablation efficiency in direct laser interference patterning of metals - Francisco Udo Marins Almeida; Bogdan Voisiat; Ignacio Tabares; Fabian Ränke; Andrés Fabián Lasagni (Scientific Reports)
Abstract This study explores the influence of the polarization angle on the formation of Laser-Induced Periodic Surface Structures (LIPSS) during Direct Laser Interference Patterning (DLIP) and its impact on ablation efficiency in stainless steel and aluminum 2024 substrates. Two pulse durations, 12 ps and 70 ps, with a laser wavelength of 1064 nm, are employed at varying accumulated fluences to evaluate their effects on the surface structuring process. The results demonstrate that the Low Spatial Frequency LIPSS (LSFL) orientation with respect to the line-like structures produced by two-beam DLIP is strongly influenced by the polarization angle and the alignment of DLIP features. In addition, the spatial period of LSFL in stainless steel remained relatively stable regardless of the polarization angle (~ 900–1000 nm), whereas in aluminum 2024, it exhibited significant variation, decreasing from approximately 920 nm to 506 nm as the LSFL rotated. The polarization angle also affected the reached structure depth at constant irradiation conditions, particularly in stainless steel, where greater depths were achieved when the LSFL aligned perpendicularly to DLIP lines (over 50% variation). These findings provide valuable insights for optimizing laser-based surface processing techniques for metallic substrates.